2019
DOI: 10.1016/j.heliyon.2019.e01566
|View full text |Cite
|
Sign up to set email alerts
|

Fast food consumption and its associations with heart rate, blood pressure, cognitive function and quality of life. Pilot study

Abstract: Background To investigate the relationship of fast food consumption with cognitive and metabolic function of adults (18–25 years old) in Riyadh, Kingdom of Saudi Arabia. Materials and Method This cross-sectional study was conducted at the College of Medicine at King Khalid University Hospital, Riyadh, Saudi Arabia. The conventionally recruited subjects underwent an evaluation that included demographic data, quality of life (wellness, stress, sleepiness, and physical act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 41 publications
(55 reference statements)
4
13
0
1
Order By: Relevance
“…21 Another study by Alsabieh etal. proposed an affirmative association between packed food products and hypertension. 22 With consumption of usually less fiber and fruits showing a significant association with PPBG and FBG in the diabetes, prediabetes, and normoglycemia groups in the present study, a study suggested the presence of heterogeneity in the associations between the ingestion of fruits and risk of type 2 diabetes. However, consumption of blueberries, grapes, and apples was significantly associated with a lower risk of type 2 diabetes.…”
Section: Discussionsupporting
confidence: 44%
“…21 Another study by Alsabieh etal. proposed an affirmative association between packed food products and hypertension. 22 With consumption of usually less fiber and fruits showing a significant association with PPBG and FBG in the diabetes, prediabetes, and normoglycemia groups in the present study, a study suggested the presence of heterogeneity in the associations between the ingestion of fruits and risk of type 2 diabetes. However, consumption of blueberries, grapes, and apples was significantly associated with a lower risk of type 2 diabetes.…”
Section: Discussionsupporting
confidence: 44%
“…Among patients with acute hypertension, obesity, smoking, and diabetes mellitus were common risk factors ( Haque et al, 2016 ). 78% of mortality is estimated due to the increased prevalence of non-communicable diseases such as cancer, diabetes, and heart disease ( Alsabieh et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…We searched for articles using several keywords, and the results are as shown in Table 1 . The actual total results were 41 articles in which of ScienceDirect 16, Emerald 12, and IEEE as many Alsabieh et al [14] , Guo et al [15] , Schilling et al [16] , Shearman and Zendulkova [17] , Van Rensburg et al [18] , Núñez Reiz [19] All "Data Governance" AND "University" Title, Abstract, Keyword 0 -All "Business Process Management" AND " University" Title, Abstract, Keyword 10 Maican and Lixandroiu [2] , Ilahi et al [3] , Dragan et al [8] , Ilahi et al [20] , Claes et al [21] , Enriquez et al [22] , Svensson and Hvolby [23] , Cojocaru et al [24] , Nikolova-Alexieva [25] , Fillies et al [26] All "Business Process Management" AND "Data Governance" Title, Abstract, Keyword 0 -Emerald All "Data Quality" AND "University" Abstract 7 Sneade [10] , Ha and Zhang [11] , Sladic et al [27] , Leng et al [28] , Campbell [29] , AlQuraan [30] , Ramsden et al [31] All "Business Process Management" AND "University"…”
Section: Phase-1mentioning
confidence: 99%